2004
DOI: 10.1136/adc.2004.064956
|View full text |Cite
|
Sign up to set email alerts
|

A drug utilisation study of antidepressants in children and adolescents using the General Practice Research Database

Abstract: were identified from the UK General Practice Research Database. Prescribing patterns, annual prevalence, morbidity patterns, and time to discontinuation of ATD use were identified. Results: A total of 24 976 subjects received 93 091 prescriptions; 51 868 (55.7%), 38 429 (41.3%), and 2708 (2.9%) prescriptions were for tricyclic antidepressants (TCAs), selective serotonin reuptake inhibitors (SSRIs), and other ATDs respectively. ATD prevalence increased 1.7-fold from 1992 to 2001. TCA prevalence decreased by 30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
80
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 20 publications
(18 reference statements)
9
80
0
2
Order By: Relevance
“…Moreover, our observations are similar to those from a UK study demonstrating a 70% increase in AD use among children between 1992 and 2001. 20 Additionally, trends in AD use according to age and sex were consistent among children from both provinces. We note a more pronounced increase in AD use among females, compared with males over the study period, consistent with observations from the recent US study.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Moreover, our observations are similar to those from a UK study demonstrating a 70% increase in AD use among children between 1992 and 2001. 20 Additionally, trends in AD use according to age and sex were consistent among children from both provinces. We note a more pronounced increase in AD use among females, compared with males over the study period, consistent with observations from the recent US study.…”
Section: Discussionmentioning
confidence: 84%
“…2 Second, the trend of increased psychotropic use has been observed among children less than 6 years old, 15,16 although others suggest that treatment in this age group is initiated only in conjunction with psychosocial services in children with predisposing risk factors. 17 More recent studies have demonstrated a continued rise in the use of psychotropics among children and adolescents both in the United States [3][4][5]18,19 and in Europe, 20,21 and these trends are seen for psychostimulants 3,4 and ADs. 5,19,20 However, there is much less data among Canadian children.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data held include subject demographic and clinical details including data on drug prescriptions and comorbid conditions.The quality of the GPRD data has been validated in a number of studies,the completeness of medical recording is reported to be high [14],and the GPRD has been used to investigate paediatric prescribing issues [12,13].…”
Section: Methodsmentioning
confidence: 99%
“…National primary care databases provide useful sources of paediatric prescribing data in the UK [12,13]. Although NICE guidance recommends that antiobesity drugs for children and adolescents be initiated from secondary care in the UK [9], routine practice is for general practitioners (GPs) to prescribe after recommendation from paediatricians.…”
Section: Introductionmentioning
confidence: 99%